Sea Level Rise Driving Increasingly Predictable Coastal Inundation in Sydney, Australia. Issue 9 (20th September 2020) - Hague, Ben S.; McGregor, Shayne; Murphy, Bradley F.; Reef, Ruth; Jones, David A.
Abstract: As global mean sea level continues to rise, thresholds corresponding to coastal inundation impacts are exceeded more frequently. This paper aims to relate sea level rise (SLR) observations and projections to their physical on‐the‐ground impacts. Using a large coastal city as an example, we show that in Sydney, Australia, frequencies of minor coastal inundation have increased from 1.6 to 7.8 days per year between 1914 and present day. We attribute over 80% of the observed coastal inundation events between 1970 and 2015 to the predominantly anthropogenic increases in global mean sea level. Further, we find that impact‐producing coastal inundation will occur weekly by 2050 under high‐ and medium‐emission/SLR scenarios and daily by 2100 under high emissions. The proportion of tide‐only coastal inundation events (i.e., where no storm surge is required to exceed flood thresholds) will increase with SLR, such that most coastal inundation events, including those considered historically severe, will become a predictable consequence of SLR and astronomical tides. These findings are important for coastal managers as frequency, severity, and predictability of inundation impacts can all now be related to the amount of SLR (e.g., a planning allowance or SLR projection). By incorporating known historical inundation events, this allows contextualization, visualization, and localization of global SLR and the changing nature of future coastal inundation risk. Plain Language Summary: As sea levels rise, the daily highest tide reaches higher and further inland, and as a result, we see coastal flooding more frequently. Coastal flooding is when roads, carparks, walking paths, gardens, and, in more extreme cases, homes and businesses are impacted by high sea levels. Using Sydney, Australia, as an example, we find that most coastal flooding events we observe today would not have happened without human‐caused sea level rise. Further, coastal flooding is expected to occur in Sydney on average once per week by 2050 and every day by 2100 if high greenhouse gas emissions continue. In the past, the most severe coastal flooding impacts, such as flooding of main roads and private property, only occurred with large coastal storm events. However, we find that these severe floods will occur much more frequently as sea levels continue to rise, as they will eventually occur on the daily high tides. As the timing and heights of daily high tides are driven by the Sun, Moon, and the seasons, these severe coastal floods will become very predictable. This will have implications for the coastal and emergency managers tasked to deal with this changing risk. Key Points: We quantify the roles that tides and increasing mean sea level have on coastal inundation in Sydney, Australia Future exceedances of current impact thresholds will be mainly tide driven, with minimal role for ocean, weather, and climate variability We develop a framework for generating projections of the frequency and severity of coastal inundation impacts, to inform adaptation